Impact of Total Quality Management on SMEs Sustainable Performance in the Context of Industry 4.0 - Ali, K. (Springer Science and Business Media Deutschland GmbH, 2022)
This empirical study analyzes the relationship of digital Total Quality Management (TQM) or Quality 4.0 practices on the sustainable performance in Malaysian small & medium (SMEs) manufacturing industries. Based on the literature review, a research model is constructed. The study hypotheses are formulated and analyzed by multiple regressions technique. The data was collected from 73 respondents at managerial levels from ISO 9000 certified small & medium manufacturing industries in Malaysia through a stratified sampling technique. The study results indicate positive and significant impact of soft TQM practices (top management commitment, customer focus and employee training) on financial, social, and environmental performance with R2 values of 0.839, 0.739 and 0.656, respectively. This study also indicates that hard TQM practices (process management, quality information analysis and advance manufacturing technology) significantly enhances financial (R2 = 0.775), social (R2 = 0.797) and environmental (R2 = 0.712) sustainable performance. In order to implement Quality 4.0 properly in SMEs manufacturing industries, industry personnel need to recognize the different role of hard and soft TQM. It is important that SMEs allocate resources to establish both type of TQM practices to achieve the effectiveness of the whole quality system. Â© 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.